2015
DOI: 10.1073/pnas.1514748112
|View full text |Cite|
|
Sign up to set email alerts
|

Role of HIV-1 matrix protein p17 variants in lymphoma pathogenesis

Abstract: Although in decline after successful anti-HIV therapy, B-cell lymphomas are still elevated in HIV-1-seropositive (HIV+) persons, and the mechanisms are obscure. The HIV-1 matrix protein p17 persists in germinal centers long after HIV-1 drug suppression, and some p17 variants (vp17s) activate Akt signaling and promote growth of transformed B cells. Here we show that vp17s derived from four of five non-Hodgkin lymphoma (NHL) tissues from HIV+ subjects display potent B-cell growth-promoting activity. They are cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
102
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(117 citation statements)
references
References 32 publications
10
102
0
1
Order By: Relevance
“…B cells were negatively isolated from unstimulated PBMCs using the EasySep Human B Cell Enrichment Kit without CD34 Depletion (Stem Cell Technologies) and were cultured in complete RPMI-1640. Cells were activated with soluble 1 μg/mL CD40L (MEGACD40L; Enzo Life Sciences) and 10 ng/mL IL-4 (R&D Systems) for 5 d. HPLC-purified HIV-1 BH10 p17 was chemically synthesized via solid-phase peptide synthesis by W. Lu, Institute of Human Virology, University of Maryland School of Medicine, Baltimore, as reported previously (12).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…B cells were negatively isolated from unstimulated PBMCs using the EasySep Human B Cell Enrichment Kit without CD34 Depletion (Stem Cell Technologies) and were cultured in complete RPMI-1640. Cells were activated with soluble 1 μg/mL CD40L (MEGACD40L; Enzo Life Sciences) and 10 ng/mL IL-4 (R&D Systems) for 5 d. HPLC-purified HIV-1 BH10 p17 was chemically synthesized via solid-phase peptide synthesis by W. Lu, Institute of Human Virology, University of Maryland School of Medicine, Baltimore, as reported previously (12).…”
Section: Methodsmentioning
confidence: 99%
“…It was recently reported that extracellular matrix protein p17 and particular genetic variants signal to B cells to enhance growth and induce chemotaxis (12,18,19). Moreover, proviral sequences for variant p17s that display B-cell growth-promoting activity can be found in HIV-NHL tissues, suggesting a role for variant p17s in lymphoma pathogenesis (12).…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…In fact, recent evidence indicates that HIV-encoded proteins endowed with peculiar biologic effects on B lymphocytes are secreted and accumulate in lymphoid tissues, mainly within lymph node germinal centers, where they may act as critical microenvironmental factors promoting lymphoma development. 7,8 Moreover, recent studies have shown that HIV viremia during highly active antiretroviral therapy is a predictor of HIV-associated lymphomas. Overall, these findings add further strength to the argument that HIV may directly contribute to lymphomagenesis.…”
Section: Introductionmentioning
confidence: 99%